Adoptive immunotherapy against ovarian cancer. Issue 1 (December 2016) - Mittica, Gloria; Capellero, Sonia; Genta, Sofia; Cagnazzo, Celeste; Aglietta, Massimo; Sangiolo, Dario; Valabrega, Giorgio
Abstract The standard front-line therapy for epithelial ovarian cancer (EOC) is combination of debulking surgery and platinum-based chemotherapy. Nevertheless, the majority of patients experience disease recurrence. Although extensive efforts to find new therapeutic options, cancer cells invariably develop drug resistance and disease progression. New therapeutic strategies are needed to improve prognosis of patients with advanced EOC. Recently, several preclinical and clinical studies investigated feasibility and activity of adoptive immunotherapy in EOC. Our aim is to highlight prospective of adoptive immunotherapy in EOC, focusing on HLA-restricted Tumor Infiltrating Lymphocytes (TILs), and MHC-independent immune effectors such as natural killer (NK), and cytokine-induced killer (CIK). Adoptive cell therapy (ACT) has shown activity in several pre-clinical models. Available preclinical and clinical data suggest that adoptive cell therapy may provide the best benefit in settings of low tumor burden, minimal residual disease, or maintenance therapy. Further studies are needed to better define the optimal clinical setting.